Anti-fat stereotypes and prejudices among primary school children and teachers in Spain - Pereda-Pereda, Eva; Echeburúa, Enrique; Cruz-Sáez, María Soledad (Anales de Psicología / Annals of Psychology, 2018)
The aim of the present study was to investigate stereotypes and prejudices among children and schoolteachers toward overweight/obesity. Two thousand fifty-five 8- to 12-year-olds and their teachers took part in the study. Children’s body mass index, children’s perceptions of overweight/obesity and teachers’ assessment of school adjustment were measured. Students, particularly younger children, ascribed less positive attributes and more negative attributes to fat figures. Furthermore, in a task to assess their behavioral intentions to participate in social and recreational activities according to target’s body size, the fat figure was the least frequently chosen. Teachers reported lower overall school adjustment for overweight/obese students. Both children and teachers showed anti-fat bias. Future research should examine cost-effective interventions to prevent anti-fat bias and to promote healthy school climate.